UJI TOKSISITAS SUBKRONIS INFUSA DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) PADA TIKUS: STUDI TERHADAP GAMBARAN MIKROSKOPIS JANTUNG DAN KADAR SGOT DARAH - Ignasius Kuncarli; Ipang Djunarko (Sanata Dharma University, 2014)
Abstract: Red betel (Piper crocatum Ruiz Pav) is one of the plants used as traditional medicinecommunity. To determine the level of safety of long-term consumption, then tested subchronic toxicity. Thestudy aimed to determine the relationship spectrum of toxic effects of infusion with changes in levels ofserum glutamic oxaloacetic transaminase (SGOT) and cardiac histopathology. The study was purelyexperimental, randomized study design complete unidirectional pattern. A total of 40 Wistar rats (20 malesand 20 females), 2-3 months were divided randomly into 4 groups: control group distilled water and 1.38;2.07; 3.105 g/KgBW of red betel leaf infusion with administration once daily for 28 days. Observationswere made before treatment and on day 28 by orbital sinus sampling through to measurement of bloodlevels of SGOT be analyzed by one way ANOVA and partially dissected mouse to see the damage to theheart. The results showed there was no significant change (p 0.05) in SGOT levels compared the controlgroup. Histology showed no specific changes were observed after administrating 28 days of red betel leafinfusion. The red betel leaf infusion did not cause significant change in SGOT level and histology of heart.Keywords : red betel, subchronic toxicity tests, SGOT, cardiac histology.